2012
DOI: 10.3171/2012.4.jns11870
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery using the Leksell Gamma Knife Perfexion unit in the management of patients with 10 or more brain metastases

Abstract: Stereotactic radiosurgery safely and effectively treats intracranial disease with a high rate of local control in patients with 10 or more brain metastases. In patients with fewer metastases, a nonmelanomatous primary lesion, controlled systemic disease, and a low RPA class, SRS may be most valuable. In selected patients, it can be considered as first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 24 publications
4
78
0
5
Order By: Relevance
“…29,35 The involvement of factors such as patient age, KPS score at SRS, and RPA class appear to have a larger impact on survival predictions than the number of metastases. 3,12,28 Tumor volume was a significant factor in patient survival, accounting for a 1-year survival increase of 14% after SRS. The clearest separation was demonstrated at < 5 cm 3 or ≥ 5 cm 3 with an increase in median survival of 4 months.…”
Section: Discussion Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…29,35 The involvement of factors such as patient age, KPS score at SRS, and RPA class appear to have a larger impact on survival predictions than the number of metastases. 3,12,28 Tumor volume was a significant factor in patient survival, accounting for a 1-year survival increase of 14% after SRS. The clearest separation was demonstrated at < 5 cm 3 or ≥ 5 cm 3 with an increase in median survival of 4 months.…”
Section: Discussion Survivalmentioning
confidence: 99%
“…A median of 2 metastases (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] were treated at each radiosurgical procedure. The median marginal dose was 18 Gy (range 10-22 Gy) and the maximum dose was 34 Gy (range 20-50 Gy).…”
Section: Radiosurgery Techniquementioning
confidence: 99%
“…8,10,11 The timing of publication of these studies coincides with an observed increase in the uptake of SRS. During our study period, multiple institutional SRS series were published, demonstrating promising efficacy for up to, and beyond, 10 intracranial lesions, [20][21][22] in elderly patients, 23 and in the postoperative setting, 24 indicating an increased practitioner comfort level with brain SRS for a number of clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery leads to tumor control in 70%-90% of metastatic brain tumors. 1,3,4,8,10 The clinical effectiveness of radiosurgery relates in part to the histological tumor source. Tumor control is adequate if serial imaging after radiosurgery reveals stable or reduced tumor volumes.…”
mentioning
confidence: 99%